2020
DOI: 10.1038/s41398-020-01101-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term cocaine self-administration on brain resting-state functional connectivity in nonhuman primates

Abstract: Long-term cocaine use is associated with a variety of neural and behavioral deficits that impact daily function. This study was conducted to examine the effects of chronic cocaine self-administration on resting-state functional connectivity of the dorsal anterior cingulate (dACC) and putamen—two brain regions involved in cognitive function and motoric behavior—identified in a whole brain analysis. Six adult male squirrel monkeys self-administered cocaine (0.32 mg/kg/inj) over 140 sessions. Six additional monke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…It reduced the blood flow to the stomach and intestines, due to which it directly effects on digestive system. It also increases the risk of ischemic colitis due to which intestine becomes injured and inflamed [30] .…”
Section: Genetic Factormentioning
confidence: 99%
“…It reduced the blood flow to the stomach and intestines, due to which it directly effects on digestive system. It also increases the risk of ischemic colitis due to which intestine becomes injured and inflamed [30] .…”
Section: Genetic Factormentioning
confidence: 99%
“…For example, presentation of a noxious thermal stimulus to squirrel monkey during ultra-high field imaging resulted in fMRI responses in numerous regions (e.g., thalamus, caudate, posterior insula) that are related to nociception in humans ( Wu et al, 2017 ). Also, repeated exposure to cocaine has been shown to alter putamen and dACC connectivity ( Kohut et al, 2020 ), a finding that recapitulates phenomena observed clinically in humans with substance use disorders ( Hu et al, 2015 ). These results suggest the existence of consistent functional networks in squirrel monkeys and humans.…”
Section: Discussionmentioning
confidence: 65%
“…For example, presentation of a noxious thermal stimulus to squirrel monkey during ultra-high field imaging resulted in fMRI responses in numerous regions (e.g., thalamus, caudate, posterior insula) that are related to nociception in humans (Wu et al, 2017). Also, repeated exposure to cocaine has been shown to alter putamen and dACC connectivity (Kohut et al, 2020), a finding that recapitulates phenomena observed clinically in humans with substance use disorders (Hu et al, 2015). These results suggest the existence of orthogonal functional networks in squirrel monkeys and humans.…”
Section: Discussionmentioning
confidence: 99%